SOME THEORETICAL AND METHODOLOGICAL CONSIDERATIONS ON HISTORICAL RESEARCH IN AND WITH ARCHIVES - Castro Valdebenito , Hugo José (2025)
This study aims to analyze how the relationship between historians and archives has been shaped at an intellectual level. It proposes an argumentative approach that examines the ways in which this relationship has been conceptualized and theorized within historiography. The focus lies in understanding archives as spaces where historical research is conducted, as well as institutions responsible for the preservation and classification of documentary sources that enable the representation of the past. In this sense, it is emphasized that archives are not merely static repositories of information, but dynamic entities that demand constant interpretation and critical reflection by their users, particularly historians. Moreover, methodological proposals are highlighted that underscore the analytical possibilities of attending to the multiple meanings embedded in the materiality of sources. And, therefore new perspectives for historiographical production are opened.